Enhanced recovery from ancient carbonate ramps: lessons and analogs from Paleozoic successions and the Persian Gulf - Jaffri, Ali R., author; Egenhoff, Sven, advisor (Colorado State University. Libraries, 2009)
Satellite imagery of the Persian Gulf, fieldwork in Kuwait and Abu Dhabi, and data from published sources are integrated to develop a thorough understanding of large-scale stratal architecture in carbonate ramps. A section of this study deals with the identification of key-surfaces in homogeneous successions. An Ordovician carbonate ramp from Sweden is selected to illustrate the importance of trace fossils in identification of maximum regression surfaces. By comparing Ordovician trace fossils from Sweden with modern crab burrows in Kuwait, a sequence stratigraphic model that shows strata architecture is presented. Oolitic facies in ancient carbonate ramps in the Devonian-Mississippian Bakken Formation that have been previously ignored or considered subtidal sheet-like deposits have been reinterpreted as coastal embayment, eolian dunes on barrier islands, and tidal channel deposits. Geometric analyses of similar environments in the modern Persian Gulf reveal that none of the oolitic facies in the Bakken Formation would be conducive to a sheet-like morphology. This paper highlights the diversity in shapes and dimensions of modern oolitic tidal channels in the Persian Gulf. Tidal channels documented in satellite imagery are oriented parallel, perpendicular or oblique to the shoreline. Planforms are remarkably similar to terrestrial fluvial systems, and transitions between straight, meandering, anastomosing, and braided patterns occur. Wide, straight channels form where bank materials consist of non-cohesive oolitic-skeletal sands, whereas those with prolific cyanobacterial growth along banks are prone to sinuous channels. A section investigates the challenges that oil and gas companies face when attempting to strike a balance between appeasing authorities and exploiting hydrocarbons while maintaining sustainable development. It also recommends policies that include amendments regarding oil fields in Kurdish territory and healthy alternatives to Production Sharing Agreements which ensure the flow of oil from Iraq while maintaining sustainable development. These include exclusion of oil fields in the Kurdish territory, which constitute only 3 percent of Iraq's oil reserves, from article 5a of the Iraqi Oil and Gas Law. This study recommends the use of contracts, such as Technical Service Agreements, that satisfy both the foreign oil companies and the Iraqi populace.
Keywords: carbonate ramps; enhanced recovery; ooids; Persian Gulf; tidal channels; geology; petroleum engineering